2017
DOI: 10.1016/j.cej.2016.08.106
|View full text |Cite
|
Sign up to set email alerts
|

Role of inherent active constituents on mercury adsorption capacity of chars from four solid wastes

Abstract: Many raw materials have active constituents for mercury removal, such as the elements oxygen (O), sulfur (S) and chloride (Cl), but these constituents are frequently neglected during the preparation process of mercury adsorbents. This study investigated the effect of various inherent active constituents of four solid wastes (waste tire, cotton straw, Chinese medicinal residue and municipal solid waste) on the mercury removal performance of their derived chars. Modification methods (chemical impregnation and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In previous study, the difference of MRE resulting from lime injection in dry or semidry scrubbing system was proved to be low 1% since inorganic material (lime) has poor adsorption capacity for mercury. ,, Moreover, the MRE of lime injection is relatively low (<22%), which is hard to determine the overall MRE (33.6–95.2%) of current APCD combinations. Instead, previous studies proved that the AC injection performed excellent adsorption capacity for mercury since the gas mercury could transform into Hg P on physical and chemical adsorption sites of AC. Then the particulate matter is captured via subsequent fabric filter. Therefore, the correlation of the MRE and AC injection amount was calculated, fitted and shown in SI Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…In previous study, the difference of MRE resulting from lime injection in dry or semidry scrubbing system was proved to be low 1% since inorganic material (lime) has poor adsorption capacity for mercury. ,, Moreover, the MRE of lime injection is relatively low (<22%), which is hard to determine the overall MRE (33.6–95.2%) of current APCD combinations. Instead, previous studies proved that the AC injection performed excellent adsorption capacity for mercury since the gas mercury could transform into Hg P on physical and chemical adsorption sites of AC. Then the particulate matter is captured via subsequent fabric filter. Therefore, the correlation of the MRE and AC injection amount was calculated, fitted and shown in SI Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…Related studies have shown that a larger specific surface area and the total pore volume help Hg 0 physical adsorption . Similarly, from Table S1, it can be seen that modification also increases the specific surface area and volume of the micropores, which greatly increases the physical adsorption capacity of the mercury sorbent to Hg 0 because the micropores are typically Hg 0 physical adsorption sites …”
Section: Resultsmentioning
confidence: 58%
“…31 Similarly, from Table S1, it can be seen that modification also increases the specific surface area and volume of the micropores, which greatly increases the physical adsorption capacity of the mercury sorbent to Hg 0 because the micropores are typically Hg 0 physical adsorption sites. 8 Similarly, modification can enrich the number of functional groups on the surface of an adsorbent. In the FTIR test results shown in Figure S1, the peak intensities of modified corn straw char at 598, 1107, 1601, and 3250 cm −1 are all enhanced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the anchoring of sulfur on ACs was not firm, hence causing leaching risks of sulfur as well as mercury adsorption products when ACs were disposed of in landfills [32,34]. Therefore, a new strategy is urgently undergoing exploration to overcome the disadvantages associated with sulfur-impregnated ACs [35,36].…”
Section: Introductionmentioning
confidence: 99%